THE USING FLASHCARDS AS MEDIA TO IMPROVE ENGLISH VOCABULARY MASTERY AT SD NEGERI 2 SAMBONG - Puspitasari, Indah; Apriyanti, Chusna; Illona Pembayun Partawidjaja, R.Vania (English Education Study Program STKIP PGRI Pacitan, 2024)
This study aims to investigate the use of flashcards as a teaching tool or media to improve English vocabulary acquisition at SD Negeri 2 Sambong. The qualitative description method was used to describe the use of flashcards in the context of English language learning at the school. This research was conducted by collecting data through direct observation, and documentation related to the use of flashcards at SD Negeri 2 Sambong. Flashcards help students in remembering, adding new vocabulary and understanding what they do not know in an interactive and fun way. The interaction between teachers and students was also seen to be more active and engaged during the use of flashcards. However, some constraints were also identified, such as the limited number of human resources who lack the understanding of English vocabulary and also the diversity of students' learning styles. This research provides a deeper understanding of the use of flashcards as a tool to improve the mastery of English vocabulary at SD Negeri 2 Sambong. The results of this study can be a reference for teachers and schools in developing effective learning strategies to improve students' mastery of English vocabulary at SD Negeri 2 Sambong